"I Would Do the Same Again": In Conversation With Biljana Plavšić. (December 2018) - Simić, Olivera
After more than 20 years in operation, the International Criminal Tribunal for the former Yugoslavia (ICTY) has closed down at the end of 2017. Biljana Plavšić made history by becoming the only woman, of 161 individuals, indicted by the ICTY. She was also the highest ranking official and the first Serb leader to plead guilty to charges raised against her before the ICTY. After entering into a plea agreement and serving two thirds of her 11-year sentence in Sweden, she returned to Belgrade in 2009 where she has been living ever since. In this article, I draw on interviews I undertook with Plavšić in the course of 2017. In the first part of the article, I briefly introduce Plavšić and situate the study within the field of international criminal justice and transitional justice. I then proceed to discuss four themes that Plavšić most frequently returned to during our conversations. These themes offer an original perspective into Plavšić's experience of being tried and sentenced by the international tribunal and her subsequent release and return home. This article aims to fill a gap in the literature by analyzing the reflections on the ICTY from its only woman defendant.